Ba Duan Jin Gymnastics to Overcome Activity Intolerance and Quality of Life in Coronary Artery Disease Patient - Diana Kusuma Astuti; Theresia Eriyani; Dyah Setyorini (Padjadjaran Acute Care Nursing Journal, 2022)
Introduction: Handling activity intolerance is a major problem in patients with CAD or cardiovascular disease. Activity intolerance and cardiovascular problems can be treated by exercising according to the prescription. One of the sports that can be applied is ba duan jin gymnastics. This mixed ba duan jin gymnastics can reduce fatigue, improve quality of life, and improve cardiorespiratory function. This case study aimed to see the progress of the patient who was given the ba duan jin gymnastics intervention. Methods: This study used a case study approach with a nursing care approach and jinn gymnastics intervention. The sample of this study is one person diagnosed with coronary artery disease, unstable angina pectoris CCS III with complaints of fatigue during activities, feeling weak, easily tired and short of breath when walking long distances who was treated in a hospital in Bandung. Result: The results of this study are that there is an increase in quality of life and a decrease in fatigue after 2 days of intervention Conclusion: Ba duan jin gymnastics can be another intervention to overcome the problems of activity intolerance, fatigue, and improve the quality of life in patients with coronary artery disease, but it needs to be implemented longer to see a more visible effect